Unveiling the gendered abyss: exploring the case of women with lymphatic filariasis and the path to inclusive care in India - Arya Rahul; Anoop C. Choolayil; Dharani Govindasamy; Gnanasekaran Vijayalakshmi; Sadhasivam Anbusivam; Vijesh Sreedhar Kuttiatt (International Journal for Equity in Health)
Abstract Introduction Lymphatic filariasis (LF), a neglected tropical disease (NTD), affects tropical regions marked by poor socioeconomic conditions and often results in non-curable filarial lymphedema. The impact of LF is often disproportionate, adversely affecting women due to a multitude of intersecting disadvantages. There has been little effort to understand the unique illness experience of women with LF. Methods To explore the interplay between gender and the illness experience of women afflicted with filarial lymphoedema, this qualitative study mapped the experience of 18 women and the perceptions of 18 men with lymphatic filariasis. Data collection involved 12 in-depth interviews and four focus group discussions, with equal gender separation. The content generated was analyzed using a hybrid thematic analysis approach. Results The study shows that individuals with filarial lymphedema, regardless of gender, encounter numerous challenges. However, certain aspects, like cultural gender norms paired with socioeconomic disadvantages, exert a disproportionate burden on women, which adversely affects their physical health, health-seeking behavior, and mental health. While the study highlights the intersectional lived experiences of women with LF, its focus on women’s experiences may limit broader generalizability across genders. Conclusions Addressing the factors that impact the lived experiences of women with lymphatic filariasis is an essential but complex task that requires positive changes across various domains. Targeted mental health interventions and robust family support systems can play a pivotal role in improving the health outcomes of affected individuals. Also, gender-informed intersectional research on the illness experiences of women with LF can give valuable insights to tailor better morbidity management policies and practices.